The conditions of choice : analysis of the decision making process on abortion in Western Ukraine - Bereza, Marta (2019)
Abortion decision making is an unavoidable process to women, who find themselves in a situation of unintended pregnancy. Such decision can be very hard to make, especially for women who live in conservative and traditionalistic societies. This study aims to look at young women’s decision making process on abortion and struggles that they face in Western Ukraine. Its’ goal is to find out what factors have an influence on decision to terminate pregnancy or keep a child and to look at the conditions in which the decision is being made. Narratives of eight women who had an experience of unplanned pregnancy in young age and decision-making on abortion are being analyzed in this study. For this research, seven respondents wrote their personal stories and one interview has been conducted. The narratives were analyzed with thematic and narrative analyses, that were used for both finding similarities throughout all of the narratives and looking at each narrative separately, studying details and specific conditions of women’s lives at the time of unplanned pregnancy. The analyses were done with the help of three theoretical approaches: Marxist feminist theory, Radical feminist theory and Intersectionality. Each one of these theories gives an explanation to the conditions of women’s lives in society by looking at the various sources of women’s oppression and discrimination. Marxist feminist theory claims that women’s position in a society won’t be equal to men’s as long as motherhood and taking care of children would be seen as primarily women’s responsibility. Such discourse not only restricts women’s access to reproduction decision making, but also limits factors that influence her decision. Radical feminist theory says that root of women’s oppression and discrimination is in patriarchy. Until the system changes and women get not only equal rights, but also equal treatment in the society, they wouldn’t be able to have full control over their lives. Intersectionality, applied to this research, offers to look at various social, economic and political characteristics of women who are facing decision making on abortion as overlapping factors influencing the decision. In conclusion, four main factors that influence the decision-making on abortion of young women in Western Ukraine have been distinguished in this study. In addition, it has been proven that all of the factors are interconnected. The narrative analysis has helped to get a closer look at the specific conditions in which young Western Ukrainian women make their decisions on abortion.